Nobilitação, parentesco e redes de poder no Centro Sul da América Portuguesa: Paulo Fernandes Viana e Francisco Alberto Rubim (cc.1750-1821) - Costa, Livia Scheiner (2020)
This work seeks to analyze personal ties as a specific dimension of the construction of power networks in the region known as the Centre-South of the Portuguese America, between the second half of the 18th century and the first twenty years of the 19th ce